Formation of a Chosŏn Buddhist Tradition: Dharma Lineage and the Monastic Curriculum from a Synchronic and Diachronic Perspective - Yongtae, Kim (Journal of Korean religions, 2020)
A new Buddhist tradition was formed in the seventeenth century in Korea that was a projection of the aim and identity of Chosŏn Buddhism at the time. Ironically, this took place during a period of great change in the international geopolitical order and during a time when wars changed the contours of East Asia. Until Chosŏn Buddhism was fully established, there were two diverging identity narratives; one that combined the various dharma lineages of the Koryŏ tradition, and the other based on the Chinese orthodox Linji lineage. In the end, the narrative of China-centered orthodoxy prevailed, which I argue to be reflective of a diachronic and synchronic situatedness. Furthermore, the monastic education that was established in the seventeenth century is examined, wherein the importance of both Sŏn and doctrine (Kyo) were openly adopted. The synchronicity of the situatedness of Buddhism and Confucianism in a close relationship of inter-adaptation is discussed through a comparison of the monastic educational process and Confucian education system. In the end, Chosŏn Buddhism was not an isolated island that was suppressed internally and isolated externally from the larger East Asian world. Past research on Chosŏn Buddhism has limited its scope to the area of Chosŏn and, relative to Confucianism, as existing under a cloud of heterodoxy and removed from the center of power. The current essay proposes the adoption of diachronic and synchronic perspectives in order to expand the scope and breadth of research on Chosŏn Buddhism, whereby an active and dynamic Buddhism can be revealed.